War and cities: how do conflicts affect urban growth dynamics? - Michel Dimou (European Regional Science Association (ERSA), 2010)
The aim of this paper is to study the impacts of wars and conflicts on city-size growth and city-size distributions. It follows recent empirical work from Davis and Weinstein (2002), Bosker and al (2008) and Dimou and Schaffar (2009) who tried to understand how wars affected the Japanese, the German and the Balkan cities-size distributions. The paper initially focuses on theoretical aspects by examining the main theories which consider the way exogenous shocks affect urban growth. Then, it uses non-parametrical methods and Markov chains in order to study city-size dynamics in the Balkan peninsula during then 1981-2005 period.
Keywords: 330